Pengungkapan Corporate Social Responsibility, Profitabilitas, Likuiditas, dan Nilai Perusahaan - Dewi, Komang Tika; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 34 No 7 (2024)DO - 10.24843/EJA.2024.v34.i07.p19, 2024)
The purpose of this study was to obtain empirical evidence regarding the effect of Corporate Social Responsibility Disclosure, Profitability and Liquidity on Firm Value. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange period 2019-2021. The sampling technique used was purposive sampling and the results obtained from the selection of samples used as objects of observation were 213 company data. The data analysis technique used is multiple linear regression analysis. Based on the analysis conducted, it was found that Corporate Social Responsibility Disclosure has no effect on firm value, profitability has a positive effect on firm value, and liquidity has no effect on firm value. This research can confirm the signal theory in relation to firm value. Keywords: Corporate Social Responsibility Disclosure; Profitability; Liquidity; Firm Value